2015
DOI: 10.1002/jmv.24292
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cannabinoids and their receptors on viral infections

Abstract: Cannabinoids, the active ingredient in marijuana, and their derivatives have received remarkable attention in the last two decades because they can affect tumor growth and metastasis. There is a large body of evidence from in vivo and in vitro models showing that cannabinoids and their receptors influence the immune system, viral pathogenesis, and viral replication. The present study reviews current insights into the role of cannabinoids and their receptors on viral infections. The results reported here indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 116 publications
2
57
0
Order By: Relevance
“…When airway epithelial cells are infected by the influenza virus, infiltration of various immune cells occurs. It is known that infiltrating immune cells are directed against infected epithelial cells, causing immunopathogenesis (Tahamtan et al, 2016 ).…”
Section: Opioids and Viral Infectionmentioning
confidence: 99%
“…When airway epithelial cells are infected by the influenza virus, infiltration of various immune cells occurs. It is known that infiltrating immune cells are directed against infected epithelial cells, causing immunopathogenesis (Tahamtan et al, 2016 ).…”
Section: Opioids and Viral Infectionmentioning
confidence: 99%
“…Their signaling has received remarkable attention because they have ability to alter immune function and effect on disease progression. [101][102][103][104] The data from our studies, for the first time, provided evidence that genetic variations in these receptors dysregulate the immune response following RSV infection and associated with risk of hospitalization in RSV-infected infants. 105,106 We showed that the genetic variations in the CNR2 gene (Q63R), which encode cannabinoid CB2 receptors, associated with RSV disease severity.…”
Section: Effects Of Variation In Opioid/cannabinoid Receptorsmentioning
confidence: 59%
“…Opioid and cannabinoid receptors (opioid receptors: μ, δ, and κ; cannabinoid receptors: CB1 and CB2) are transmembrane G protein‐coupled receptors with an affinity for endogenous and exogenous peptides. Their signaling has received remarkable attention because they have ability to alter immune function and effect on disease progression . The data from our studies, for the first time, provided evidence that genetic variations in these receptors dysregulate the immune response following RSV infection and associated with risk of hospitalization in RSV‐infected infants .…”
Section: Introductionmentioning
confidence: 69%
“…Particularly in viral infections, the anti-inflammatory activity of D 9 -tetrahydrocannabinol (D 9 -THC), 2 the main component of cannabis, may jeopardize host immune responses to acute viral infections, leading to disease progression and death in the worst case. 3,4 Nonetheless, D 9 -THC may be beneficial in viral infections where the host inflammatory response is pathogenic, 3 although its psychoactive and addictive potential is a significant limitation to its therapeutic development.…”
Section: Introductionmentioning
confidence: 99%